Temperature Dependence of Photodegradation of Dissolved Organic Matter to Dissolved Inorganic Carbon and Particulate Organic Carbon - Porcal, Petr; Dillon, Peter J; Molot, Lewis A (PloS one, 2015)
Photochemical transformation of dissolved organic matter (DOM) has been studied for more than two decades. Usually, laboratory or "in-situ" experiments are used to determine photodegradation variables. A common problem with these experiments is that the photodegradation experiments are done at higher than ambient temperature. Five laboratory experiments were done to determine the effect of temperature on photochemical degradation of DOM. Experimental results showed strong dependence of photodegradation on temperature. Mathematical modeling of processes revealed that two different pathways engaged in photochemical transformation of DOM to dissolved inorganic carbon (DIC) strongly depend on temperature. Direct oxidation of DOM to DIC dominated at low temperatures while conversion of DOM to intermediate particulate organic carbon (POC) prior to oxidation to DIC dominated at high temperatures. It is necessary to consider this strong dependence when the results of laboratory experiments are interpreted in regard to natural processes. Photodegradation experiments done at higher than ambient temperature will necessitate correction of rate constants.
Keywords: kinetika; pevné částice; huminové látky; statistické modely; Light; uhlík; světlo; Photolysis; Oxidation-Reduction; Carbon; Humic Substances; Models, Statistical; Temperature; fotolýza; Particulate Matter; Kinetics; oxidace-redukce; Solubility; rozpustnost; teplota